Cultural Influences and Editorial Messages, or on a "Wonderful Game of Changeable Fate": Observations on the Short Story "Innocent Sinners" - Vladimir Ignatov (Zeszyty Cyrylo-Metodiańskie)
The paper attempts to analyze the translated short story “Innocent Sinners” (“Balgarska dnevnitsa”, no 13 & 14, 1857). Its main purpose is to summarize the romantic and didactic messages of the work embodied in the speech and actions of the characters. The cultural influences in the editorial decisions of Danilo Medakovich and Georgi Rakovski have been analysed as well. The ideology and themes represented in the short story are examined in the context of the narrative models that lay the foundations for the appearance of original Bulgarian fiction. The research reveals and contextualizes the moral dimensions of the leading plot (love – duty – unfaithfulness – revenge – forgiveness in death). The conclusion is that despite its modest place in the national literary process, “Innocent Sinners” belongs to “the narrative of brotherhood between neighboring nations” (Nadezhda Alexandrova). Original title in Bulgarian: Междукултурни влияния и редакторски послания, или за една „чюдесна игра на непостоянная съдбина“ (наблюдения върху разказа „Невинни грешници“).